DIFFERENTIATED ASSIGNMENTS AS THE LEARNING ACTIVITY MOTIVATING FACTOR IN THE TRAINING OF FUTURE PRESCHOOL TEACHERS - Kushnir, Svitlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The articles’s aim is to describe the features of introducing differentiated assignment for homework and classroom work and their impact on the activation of cognitive, social, professional, value motives of the training of future preschool teachers in the pedagogical process of the university. The analysis of scientific research in this area allows us to state that the differentiation of teaching materials, the provision of the student with the choice of the complexity of the assignment, the establishment of constructive feedback are an integral part of the motivational environment that should ensure the student's active personal position in the process of cognitive constructive activity. Differentiation of training during the classroom allows to ensure the assimilation by all students of the educational content, which assumes an invariant (mandatory part of the program material) and an optional part that involves the complexity of assignments. The main goal of differentiation in teaching is to determine the most rational nature of the work for each student, relying on their individual characteristics, preferences, abilities, time frames. Thus, the training of future preschool teachers with the help of differentiated tasks becomes important for them, the desire to comprehend the foundations of the profession, to learn, to interact with peers and the teacher.The author experimentally confirmed that the introduction of a differentiated approach to the development of content and its implementation in the practice of training future preschool teachers in higher school conditions contributes to improving the effectiveness of the educational process by activating cognitive, professional, social and value motivations of students, taking into account their individual inclinations and preferences.The methodological basis of the research was the theoretical analysis of scientific literature on the problem; empirical research methods (pedagogical experiment, observation, interview, testing by the method of studying the educational activity motives (modification A.A. Rean & V.A. Yakunin)); statistical methods of processing results (the calculation of percentages, ranking).